2009
DOI: 10.1021/ie801474q
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Mustard (Brassica juncea L.) Protein Isolate and Recovery of Phenolic Compounds by Ultrafiltration

Abstract: Mustard (Brassica juncea L.) seed meal is good source of protein (28-36%) and phenolic antioxidants like sinapic acid and sinapine. In this work an ultrafiltration-diafiltration-based technique is developed for simultaneous preparation of protein isolate and recovery of phenolic rich fraction from seed meal using a high shear rotating disk membrane module with emphasis on reduced membrane fouling effect. The yield of membrane process found less (31.4% on dry basis) compared to precipitation process (42% on dry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 31 publications
1
36
0
Order By: Relevance
“…Amino acid composition of the end product (bread) supplemented with the SMPI was analyzed according to the method described in (Das et al 2009). Before amino acid analysis, each bread sample was hydrolyzed in 6.0 N HCl.…”
Section: Amino Acid Compositionmentioning
confidence: 99%
“…Amino acid composition of the end product (bread) supplemented with the SMPI was analyzed according to the method described in (Das et al 2009). Before amino acid analysis, each bread sample was hydrolyzed in 6.0 N HCl.…”
Section: Amino Acid Compositionmentioning
confidence: 99%
“…It has been shown that more than 70% of total phenolic content is sinapin, the cholin ester of sinapic acid (Amarowicz et al, 1996;Das et al, 2009). There are several research papers highlighting the effectiveness of ground mustard seed or its extracts in preventing oxidation processes in raw and cooked chicken meat and meat products (Shahidi et al, 2007;Kumar and Tanwar, 2011), but only a few about pork samples (Saleemi et al, 1993;Mc Carthy et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…2 kDa and 1 kDa fractionations were performed in RDM. Details of membrane module methodologies are accessible in our previous study (Das, Bhattacharjee, & Ghosh, 2009b, 2009c. Specifications of the membranes used are presented in Table 1.…”
Section: Membrane Modules In Use For Uf Fractionationmentioning
confidence: 99%